Aflatoxin M1 contamination of milk in the greater Addis Ababa milk shed, Ethiopia - Szonyi, Barbara; Gizachew, D.; Tegegne, Azage; Hanson, Jean; Grace, Delia (International Livestock Research Institute, 2015)
Aflatoxins are a group of toxic metabolites produced by Aspergillus molds that contaminate a variety of food and animal feeds. Exposure to aflatoxins causes serious illness in humans, including liver cancer and stunting in children. When cows ingest aflatoxin-contaminated feed, they secrete aflatoxin M1 (AFM1) in their milk. Aflatoxin M1 has been detected in high concentration throughout sub-Saharan Africa in cow’s milk and in human breast milk, putting infants at high risk. In Ethiopia, a currently ongoing study has revealed high levels of contamination of dairy feeds with aflatoxins in the Greater Addis milk shed. In this study, we have collected raw milk samples from dairy farmers and milk collectors in the Greater Addis milk shed and quantified the levels of AFM1 using enzyme-linked immunosorbent assay (ELISA). Using a cross-sectional study design, a total of 100 raw milk samples were collected from dairy farms in Addis Ababa and its surrounding areas (27 from Addis Ababa, 23 from Debre Zeit, 9 from Sebeta, 31 from Sendafa and 10 from Sululta). All the milk samples were contaminated with AFM1 and most (92%) of the samples had aflatoxin levels exceeding 50 ppt, which is the FAO/WHO and EU permissible level of AFM1 in milk. The highest AFM1 content was 4977 ppt and the lowest was 28 ppt. In addition, ten raw milk samples were collected from milk collectors located in Addis Ababa (1), Debre Zeit (3) and Sululta (6). All of the samples from milk collectors were contaminated with AFM1 exceeding 50 ppt. The high levels of AFM1 in milk in the Greater Addis milk shed is alarming, because it is one of the largest milk sheds in the country, and most residents of Addis Ababa get their milk from these sources. Children in particular are encouraged to drink milk as much as possible. Considering that young children are weaned on to cow's milk and they are not immune-competent at this early age, consumption of milk contaminated with AFM1 may further suppress their immunity and also contribute to stunting. In addition, it has been estimated that aflatoxins may play a causative role in up to 30% of the cases of liver cancer globally each year. Therefore, the high level of aflatoxin contamination in the peri-urban dairy value chain of Addis Ababa requires urgent response to reduce human and animal exposure to these toxins. Our research group is currently testing intervention strategies to address the problem of aflatoxins in dairy feed in Ethiopia.